2011
DOI: 10.1097/dad.0b013e3181ef2d65
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiectases Are Common Underlying Warts and in Normal Peritumoral Skin: Histologic Evidence of Decreased Immune Surveillance

Abstract: Minor trauma and solar elastosis from chronic ultraviolet radiation exposure are likely the etiologic factors in the development of lymphostasis. By decreasing immune surveillance, latent lymphedema ostensibly facilitates human papillomavirus infection and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The acquisition of solar elastotic material also disrupts lymphatic drainage, which may also play a role in decreased immunity [32]. We found that tumors removed from the head and neck expressed lower levels of CD3ε, CD25, ICAM-1, and IFN-γ mRNA compared to tumors from other sites.…”
Section: Discussionmentioning
confidence: 73%
“…The acquisition of solar elastotic material also disrupts lymphatic drainage, which may also play a role in decreased immunity [32]. We found that tumors removed from the head and neck expressed lower levels of CD3ε, CD25, ICAM-1, and IFN-γ mRNA compared to tumors from other sites.…”
Section: Discussionmentioning
confidence: 73%
“…In fact, in normal perimelanoma skin, lymphatic vessels are significantly dilated compared with normal skin surrounding nonmelanoma skin cancers and benign skin tumors attesting to impeded lymphatic drainage and compromised lymphatic function [30]. Thus, we conclude that impaired lymphatic function in the elderly may prevent melanoma cells from trafficking to the SLN, but also may …”
Section: Discussionmentioning
confidence: 93%
“…We found lymphangiectasias in the surrounding dermis, suggesting local lymphostasis and decreased immune surveillance as postulated by Paul and Carlson. 16 The fibrosis in LCFV may contribute to a maladaptive immune reaction that prevents normal transport of foreign antigen to a draining lymph node. The absence of any reaction in a friend of the patient who received an identical tattoo at the same time indicates the importance of unique host factors in this reaction.…”
Section: Discussionmentioning
confidence: 99%